Pengaruh Fisiotaping Terhadap Peningkatan Kemampuan Fungsional Pada Pasien Osteoarthritis - Afrianti Wahyu Widiarti; Sukadarwanto Sukadarwanto (Jurnal Keterapian Fisik, 2016)
Abstract: Osteoarthritis, Knee, Fisiotaping, Functional Activity. The aims of thestudy was to finded the effect of fisiotaping to increased functional activity inpatients with osteoarthritis of the knee. a research design that is used is Onegroup pre and post design with control. The research subjects 20 people whosuffer from osteoarthritis of the knee who met the study criteria given fisiotapingduring 6 weeks of treatment. The research location is Clinic of YPAC Surakarta,Central Java. Measuring Tool used WOMAC Scale. the functional activity(WOMAC) normality test of data, data are normally distributed then tested withpaired sample t test. The results of the functional significance of the activitybefore and after the treatment has a value of p = 0.000 (p <0.05), which meansthere fisiotaping effect of increased functional activity.